Mechanics of left ventricular systolic and diastolic function in physiologic hypertrophy of the athlete's heart - Colan, S. D. (Cardiology Clinics, 1997)
As a result of a number of factors, there is tremendous diversity in the pattern of cardiac mechanics encountered in athletes. Nevertheless, several trends can be identified, and several conclusions are possible. Hypertrophy of a mild to moderate degree and out of proportion to body size is a common finding. Some athletes experience ventricular dilation with appropriate hypertrophy and preservation of the ventricular mass-to-volume ratio, whereas others manifest concentric hypertrophy with an increased mass-to-volume ratio. The functional changes that are encountered appear to be secondary to the structural alterations, and there is no evidence of altered myocardial systolic or diastolic properties. Some athletes with hypertrophy have reduced wall stress when they are evaluated at rest, and velocity of shortening is augmented because of the reduced afterload. As a result of adaptation to a high-output state, some athletes appear preload reduced when evaluated at rest. Although velocity of shortening is not affected by preload status, fractional shortening is inversely related to preload. The magnitude of systolic shortening is therefore the net result of altered preload and afterload and cannot be understood without assessing both of these parameters. When the various determinants of systolic shortening are included, contractility appears to be normal. There have been several reports of depressed contractility immediately after extreme exertion. Although the mechanism remains uncertain, several intriguing possibilities have been proposed.